The trans-Neptunian object size distribution at small sizes - Gil Hutton, Ricardo Alfredo (2009)
Aims. The aim. of this work, is to estimate the size distribution of small Trans-Neptunian objects. Methods. We simulate the irradiation and collisional processes affecting the surface of a Trans-Neptunian object for the first time using as a constraint the peculiar crystalline to amorphous water ice ratio observed on (136108) 2003 ELa. Results. We find that the size distribution changes its exponent from q0 = 4.2 at larger sizes to q1 = 2.40 ± 0.3 at the smaller ones, with a break, radius of r1 = 35 ± 15 km. If this size distribution is applied to studying the collisional surface evolution of (1361.08) 2003 EL61, we find that the object must be covered by a thin ice crust of ≈0.12 cm, while the original, composition of the object is still present at 1.61 cm or more below the surface. This result is not affected by a collision with a large projectile that occurred by chance more than 109 yr ago since after a short time the mean value obtained for the crystalline to amorphous water ice ratio is indistinguishable from the one obtained without a collision with a large projectile. Since the simulations are not sensitive to the effects of very small projectiles (rp < 10-30 m), it is possible that the exponent of the size distribution for these very small, objects changes again, approaching a Donhanyi's size distribution.